Design of Binary and Ternary Logic Inverters Based on Silicon Feedback FETs Using TCAD Simulator - Ashkan Horri (IET Circuits, Devices and Systems)
A feedback field effect transistor (FBFET) with p-n-p-n structure benefits from a positive feedback mechanism. In this structure, the accumulated charges in its potential well and limitation of carrier flow by its internal potential barrier lead to superior electrical properties such as lower subthreshold swing (SS) and higher ION/IOFF ratio in comparison with FinFET. Thus, FBFET is a promising alternative for digital applications such as logic inverters. In this paper, binary and ternary logic inverters are designed by using FBFETs with 40 nm channel length. The doping profile in the device plays an essential role and specifies the binary or ternary operation of the inverter. The inverter is analyzed by using a TCAD mixed-mode simulator. The results indicate the high value of 1010 for ION/IOFF ratio with an extremely low SS (1 mV/decade). The voltage transfer characteristics of the inverter and its dependence on doping levels have been investigated. Also, the electrical properties of this inverter are compared with previous inverter counterparts.